2002
DOI: 10.1002/ijc.10296
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p53 and its homologues in primary and recurrent squamous cell carcinomas of the head and neck

Abstract: The tumour-suppressor protein p53 belongs to a family that includes 2 structurally related proteins, p63 and p73. Because of their structural homology, it has been hypothesized that both homologues serve as "spare mechanisms" in p53 mutations to regulate the cell cycle by inducing apoptosis. We investigated the mutational and protein expression status of p53 in correlation to its homologues, p73 and p63, in primary and recurrent squamous cell carcinomas of the head and neck (HNSCC) and corresponding nonneoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
51
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 27 publications
14
51
1
2
Order By: Relevance
“…The core domain consisting of the b-strand and the first a-helix shows a tetrameric arrangement similar to that of the p53 OD. The transition from the last turn of helix I with a 3 10 -helical geometry to helix II occurs over Pro 382. Helix II of monomer A (as defined in Figure 3) reaches across the tetrameric interface and forms hydrophobic interactions with helix I of monomer C encompassing Leu 377, Leu 380, Val 381, Leu 385, Val 386 and Tyr 389.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The core domain consisting of the b-strand and the first a-helix shows a tetrameric arrangement similar to that of the p53 OD. The transition from the last turn of helix I with a 3 10 -helical geometry to helix II occurs over Pro 382. Helix II of monomer A (as defined in Figure 3) reaches across the tetrameric interface and forms hydrophobic interactions with helix I of monomer C encompassing Leu 377, Leu 380, Val 381, Leu 385, Val 386 and Tyr 389.…”
Section: Resultsmentioning
confidence: 99%
“…5 p73 is further known as an important inducer of apoptosis in response to DNA damage. 6 Although only few mutations of p63 and p73 have been found in human tumors so far, overexpression of p63 is often observed in squamous cell carcinoma, [7][8][9][10] which has been shown to suppress p73-dependent apoptosis. 11 Among all p53 family members, including those from invertebrate species, the DNA binding domain is the most conserved domain, [12][13][14][15] followed by the oligomerization domain (OD), which is indispensable for the biological function of all p53 protein family members.…”
mentioning
confidence: 99%
“…In other cases, overexpression of p63 appears to involve mechanisms independent of genomic amplification (Redon et al, 2001). In any event, numerous studies have demonstrated p63 overexpression in up to 80% of primary head and neck squamous cell carcinomas (HNSCCs), and p63 overexpression is also commonly observed in other squamous epithelial cancers, including lung, nasopharyngeal, esophageal and cervical cancers (Wang et al, 2001; p63 and p73 in human cancer: defining the network MP DeYoung and LW Ellisen Hu et al, 2002;Weber et al, 2002;Massion et al, 2003;Sniezek et al, 2004). Reports have varied as to the frequency of p63 expression in invasive breast carcinomas, with studies ranging from 0 to 30% (Wang et al, 2002;Reis-Filho et al, 2003;Koker and Kleer, 2004;Ribeiro-Silva et al, 2005).…”
Section: Expression and Mutation Of P63 And P73 In Human Cancermentioning
confidence: 99%
“…9 Such a role for p63 in tumors was supported by the observation that ∆Np63α, the major isoform expressed in normal basal epithelial cells, is highly expressed in up to 80% of primary head and neck squamous cell carcinomas (HNSCCs), as well as in squamous epithelial malignancies of the lung and esophagus. [14][15][16][17] Indeed, the genomic locus on chromosome 3q that harbors p63 is found to be amplified in a subset of these cases. 18 In addition, immunohistochemical analysis suggests that aberrant p63 expression may be an early event in the pathogenesis of HNSCC, as extension of normal basal p63 expression into the suprabasal levels is observed in mucosal specimens exhibiting dysplasia, a premalignant lesion (ref.…”
Section: Proposed Contributions Of P63 and P73 To Tumorigenesismentioning
confidence: 99%